A Comparison of Kinematic Symmetry of Lower Limbs during Running at Different Speeds - fatahi, Ali; Molavian, Rozhin; Salehi, Mehrangiz; Alizadeh, Razieh (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Symmetry and asymmetry of lower limbs are introduced as main critical challenges of human movement. The aim of this study was to compare the kinematic symmetry of lower limbs during running at different speeds. Material and Methods: The study was conducted as a quasi-experimental design. Twenty-eight professional runners (aged: 34.75±6.63 years) voluntarily participated in this study. Running at three progressive speeds (2.5, 3.5 and 4.5 m/s) was conducted by each subject on a treadmill while kinematic data were captured at 150 Hz. Peak angle of hip, knee and ankle joints during flexion were derived in the stance phase of running. Independent T-test were performed to examine the symmetry of peak flexion angles of hip, knee and ankle joints during running at different speeds using SPSS ver. 22 (P<0.05). Results: Findings showed no significant difference between two limbs in peak flexion angles of lower joints at every speed. Conclusions: Symmetry exists in peak flexion angles of lower joints in stance phase during running at the different progressive speeds. Coaches and biomechanists would achieve benefits of kinematic symmetry of lower joints in order to prevent injuries and optimize athletes’ running performance.